Assessment of IL-27 as a Predictive Biomarker for Immune Response in Asthmatic Patients in Diyala Governorate - Salman, Ahmed; Jaber, Hind; Saddam, Ekhlas (University of Thi-Qar Journal of Science, 2025)
Asthma is a persistent inflammatory respiratory disease characterized by coughing, wheezing, and intermittent dyspnea, as well as a sensation of chest tightness. The relationship between interleukin-27 (IL-27) and asthma is not precisely known yet. This study attempted to estimate the serum level of IL-27 and its relationship with immunological and inflammatory markers in patients suffering from asthma. The demographic characteristics of this study were analyzed statistically. The serum levels of IL-27 were evaluated by Enzyme-linked immunosorbent assay (ELISA). CRP and Total IgE were evaluated by Cobas C111 and Cobas E411, respectively. The study showed a highly significant difference in IL-27, CRP, and total IgE when we compared between the patient group (62.12 ± 16.58 pg/ml, 11.2 ± 6.29 mg/l, and 297.26 ± 86.6 IU/ml), and the healthy control group (39.32 ± 3.576 pg/ml, 2.49 ± 1.1 mg/l, and 93 ± 18.3 IU/ml) respectively. ROC analysis of the studied biomarkers showed high sensitivity and specificity. That observation of elevation in all studied biomarker levels in asthma patients indicates a strong evidence in the diagnosis of asthma, as well as in the differentiation between acute and chronic cases, and in determining the severity of asthma.